Plastic particles adsorb to the roots of freshwater vascular plant Spirodela polyrhiza but do not impair growth - Dovidat, Lena C.; Brinkmann, Bregje W.; Vijver, Martina G.; Bosker, Thijs (Limnology and oceanography letters, 2020)
We investigated the effect of nano‐ and microplastics on the freshwater duckweed species Spirodela polyrhiza, a vascular plant. S. polyrhiza was exposed for 120 h to concentrations ranging from 102 to 106 particles·mL−1. We assessed effects on growth and chlorophyll production, and explored adsorption and absorption by way of confocal microscopy. For both nano‐ and microsized particles, no concentration‐dependent effects on growth were found (expressed as fresh weight, frond, and root sizes). In addition, chlorophyll concentrations were not significantly affected. Confocal microscopy indicated that nanosized plastic particles adsorbed externally to the duckweed, especially to the roots. Internalized plastic particles could not be detected. Nevertheless, given their important role in ecosystems as a food source for a range of organisms, the adsorption of plastic particles to S. polyrhiza roots as detected in this study can result in the transfer of plastic particles to diverse herbivorous species within the ecosystem.